Exploring Aminopenicillin Resistance in Uropathogenic Escherichia Coli and Optimized Lead Prediction to Overcome Resistance Through New Generation Tools - Shrestha, Sabin; Adhikari, Barsha; Thapa, Rahi Bikram; Adhikari, Pharsuram; Bajracharya, Mijala; Giri, Usha; Khanal, Dharma Prasad (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Urinary tract infections (UTIs) are a prevalent condition caused by bacteria such as Escherichia coli, Klebsiella, Proteus, Staphylococcus, Enterococcus, and Pseudomonas aeruginosa species. According to the Ministry of Health and Population’s 2079/80 annual report, Nepal recorded 5,284 cases of UTI-related morbidity. The growing burden of infectious diseases and antimicrobial resistance poses a significant threat to public health. Method: A retrospective, descriptive cross-sectional study was conducted at a tertiary care hospital in Kathmandu, Nepal, from July 2023 to January 2024. A purposive sampling technique was employed, and the collected data were analyzed using various standard software, web servers, and statistical modules. Results: Out of 3,000 urine samples, 246 exhibited significant bacterial growth. Among the isolates, Escherichia coli, the predominant Gram-negative bacterium (63.4%), demonstrated 88.46% resistance to amoxicillin. Similarly, Staphylococcus aureus, the dominant Gram-positive isolate (6.3%), showed 50% resistance to ampicillin, indicating a rising trend of resistance to aminopenicillins. Conclusion: Amino Penicillin resistance in Escherichia coli species is at high levels, BA-3 and BA-10 emerges as a promising candidate with better physiochemical and pharmacokinetics parameters for future therapeutic development. Experimental validation and exploration of additional resistance mechanisms are recommended for comprehensive treatment strategies.